2021
DOI: 10.1177/23780231211009983
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Eviction Filing Patterns in 2020

Abstract: The coronavirus pandemic precipitated an economic crisis disproportionately affecting renter households. Attempting to prevent a surge in evictions, policy makers at the federal, state, and local levels extended emergency protections to renters. The authors describe eviction filing patterns in 2020 and analyze the efficacy of eviction moratoria. New filings were reduced dramatically since the start of the pandemic. Between March 15 and December 31, 2020, across sites for which data are available, 65 percent fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Our database documents the dates that forty-three US states and DC instituted and lifted eviction moratoria. These data were analyzed to demonstrate the associations between eviction moratoria and COVID-19 incidence and mortality [ 23 ], mental health outcomes [ 24 ], and eviction filing rates [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our database documents the dates that forty-three US states and DC instituted and lifted eviction moratoria. These data were analyzed to demonstrate the associations between eviction moratoria and COVID-19 incidence and mortality [ 23 ], mental health outcomes [ 24 ], and eviction filing rates [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…With renters accumulating large rental debts during the COVID-19 crisis, 16 eviction moratoriums were often the only thing preventing tenants from immediate housing loss. 17 Given the strong ties between housing insecurity and mental health, these moratoriums may also have served to protect renters’ mental health. Accordingly, 1 prior study found that living in a state with an eviction moratorium was associated with lower levels of mental distress among Black survey respondents, although the association did not hold for the overall sample.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, housing precarity and the risk of eviction as a result of the COVID-19 pandemic has the potential to reach unprecedented levels, further exacerbating housing inequities and endangering public health (Gold, 2016;Rice & Oliva, 2021). For example, as various eviction moratoriums throughout the US have lapsed during the pandemic, eviction filings have exceeded historical averages (Hepburn et al, 2021). Emerging evidence suggests that COVID-19 eviction moratoriums have helped to mitigate the spread of the virus and prevent housing displacement, though much of this evidence is preliminary and more work in this area is needed (Benfer et al, 2020;Jowers et al, 2021;Leifheit et al, 2020;Nande et al, 2021).…”
Section: Introductionmentioning
confidence: 99%